2004
DOI: 10.1007/s10350-004-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Complete Pathologic Response Following Preoperative Chemoradiation Therapy for Middle to Lower Rectal Cancer Is Not a Prognostic Factor for a Better Outcome

Abstract: Tumor response following preoperative chemoradiation therapy is mainly related to the preoperative regimen used. For patients receiving preoperative chemoradiation therapy, pretreatment T stage, but not tumor response to preoperative chemoradiation therapy, is prognostic for outcome (both disease-free and overall survival).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 36 publications
7
121
1
2
Order By: Relevance
“…6,20 In brief, patients underwent to external beam RT with a 10-18 MV linear accelerator. The clinical target volume included the primary tumor, with the mesorectum, the posterior walls of the bladder and prostate/vagina, and the internal iliac nodes.…”
Section: Study Design and Patients Enrollmentmentioning
confidence: 99%
“…6,20 In brief, patients underwent to external beam RT with a 10-18 MV linear accelerator. The clinical target volume included the primary tumor, with the mesorectum, the posterior walls of the bladder and prostate/vagina, and the internal iliac nodes.…”
Section: Study Design and Patients Enrollmentmentioning
confidence: 99%
“…The more important endpoints of overall survival, relapse free survival, local recurrence, and distant recurrence are yet immature for most trials and are pending longer follow-up periods. The validity of path CR as a surrogate for long term oncologic outcome has not been firmly established in this disease site and conflicting reports as to the prognostic significance of path CR exist in the literature [21][22][23] . Path CR rates reflect response to neoadjuvant therapy only; however long term outcome may also be influenced by the intensification of adjuvant therapy in trials such as this.…”
Section: Discussionmentioning
confidence: 99%
“…Those patients with nodal downstaging also had better 5-year local control (84.3%), PFS (67.1%) and OS (74.3%) than those who did not have nodal downstaging (72%, 42.2% and 56.1%, respectively). On the other hand, Salvatore Pucciarelli et al have not found statistically significant differences for PFS and OS on comparing the actuarial survival curves of patients with different tumor responses to preoperative treatment, whether evaluated as tumor regression grade or as pTNM stage (Pucciarelli, 2004). It was in this context that we developed a single-institute study to evaluate the therapeutic response and impact on survival of preoperative RT, alone or combined with chemotherapy, in patients with locally advanced rectal cancer.…”
Section: Prognostic Factors For Responders To Chemoradiationmentioning
confidence: 95%